Different axis approaches for ultrasound-guided centrally inserted central catheterization in children: a systematic review and meta-analysis of randomized controlled trials - Lee, In Kyung; Lee, Kyeong Hun; Han, Hye-ji; Choi, Jieun; Kim, Na Jin; Kim, Kyunghoon (Frontiers in Surgery, 2025)
BackgroundCentrally inserted central catheterization (CICC) is a critical procedure in pediatric care. However, CICC in children poses greater challenges compared to adults due to anatomical and physiological differences, leading to higher complication rates. Ultrasound-guided approaches have been developed to enhance the safety and effectiveness of CICC, but the comparative efficacy of different axis approaches remains unclear.MethodsA systematic review and meta-analysis of randomized controlled trials comparing different axis approaches for ultrasound-guided CICC in children was conducted. Searches were carried out in databases up to June 10, 2024. Six studies were included in the systematic review and three studies were included in the meta-analysis. Primary outcomes included first-attempt success rate, overall success rate, and cannulation time. Secondary outcomes were complications such as hematoma and posterior wall puncture.ResultsData from 547 children were analyzed. The long-axis in-plane approach significantly reduced cannulation time (MD −27.48 s, 95% CI, −33.99 to −20.97) and overall complications OR 0.21, 95% CI, 0.1–0.48) compared to short-axis out-of-plane approach. No significant differences were found in first-attempt or overall success rates between the long-axis and short-axis approaches.ConclusionThe long-axis approach for ultrasound-guided CICC in children offers significant advantages in reducing cannulation time and complications. While dynamic needle tip positioning method may serve as an alternative to in-plane methods, further studies are needed to validate its clinical efficacy. Further research is needed to refine these techniques and explore their application in diverse clinical settings.